UJI PRODUKTIVITAS JAMUR MERANG (Volvariella volvaceae) BIBIT F3 CILAMAYA DAN KONSENTRASI MEDIA TANAM AMPAS TAHU - Gita Erina Apriyanti Widiyanto; Ani Lestari; Yayu Sri Rahayu (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
Karawang is a rice center in West Java and National, rice straw potentially used as a media for merang mushroom to grow. In research, tofu pulp planting media was carried out and tested the productivity of the merang mushroom F3 seedlings from Cilamaya. The purpose of the research to obtain the composition of the tofu pulp growing media which gave the highest result towards merang mushroom growth. The research was conducted in Plant Biotechnology Laboratory, Faculty of Agriculture, Singaperbangsa Karawang University and in Kumbung (Mushroom House), Pasirmulya Village, Majalaya, Karawang. The method that is used was experimental, single factor randomized block design (RBD) of 6 treatments in 4 replications, the treatments were: A (Control + Straw 100%), B (Tofu pulp 5% + straw 95%), C (Tofu plus 15% + straw 85%), D ( tofu pulp 25% + straw 75%), E (tofu pulp 35% + straw 65%) and F (tofu pulp 45% + straw 55%). The results showed that treatment C (15% tofu pulp + 85% straw) has the best value, there is a significant effect on the parameters of fruit body length of 6,98 cm, fruit body diameter with a value of 18,22 mm, number of fruit bodies with a value of 5,80, fruit body weight 10,05 g.